Restorative Justice in Child Rape Perpetrators: A Case Study on Perpetrators With Intellectual Disability - Wahyu Saefudin; Rony Aryono Putro; Sriwiyanti Sriwiyanti (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The main role of probation officers is implementing restorative justice for the juvenile. However, a rape perpetrator with intellectual disability will encourage a different approach. Therefore, this study aims to explain how the application of restorative justice by probation officers on youth offenders with intellectual disabilities. The method used in this study is an empirical normative method. Primary legal materials were obtained through interviews with probation officers tasked with assisting in the investigation, prosecution, and examination in court, to assist in implementing decisions. Another source of legal materials was also obtained through the document of community research. Finally, secondary legal materials were obtained from various sources such as legislation, library books, and scientific journals. The results show three primary points. First, probation officers have realized restorative justice through their role in community research and mentoring. Second, probation officers provide recommendations for the rehabilitation of offenders. Third, probation officers reinforce other law enforcers such as police, prosecutors, and judges to conduct psychological diagnoses to ensure the child’s condition. However, this study also finds that not all law enforcers can understand and handle children with intellectual disabilities.